Molecular Identification of Bipolaris cactivora on Dragon Fruit in Thailand - Oeurn, Samoul; Jitjak, Wuttiwat; Sanoamuang, Niwat (วารสารแก่นเกษตร, 2016)
A fruit rot disease observed in white-fleshed dragon fruit, Hylocereus undatus (Haworth) Britton & Rose, collected from Loei province, Thailand was studied to identify the causative agent. Common symptoms on the surface of the fruits were water-soaking brown spots with powdery signs. The diseased fruits were then isolated for the fungal pathogen. According to the morphology, Bipolaris cactivora (Petr.) Alcorn was the most possible one that caused the disease. To confirm this, the molecular identification and phylogenetic analysis using two gene sequences, internal transcribed spacer (ITS) amplified with ITS1 and ITS4 primers and elogation factor (EF) using 983F and 2218R primers were thus employed. Due to the statitical supports of high bootstrap score at 99% derived from Neighbour-joining method and potential interior propability, 100% calculated fron Baysian analysis, the fungal pathogen of rot disease on the dragon fruits was B. cactivora.